Inhibition of the adenine nucleotide translocator by N-acetyl perfluorooctane sulfonamides in vitro - O'Brien, Timothy M. (2008)
N-alkyl perfluorooctane sulfonamides have been widely used as surfactants on fabrics and papers, fire retardants, and anti-corrosion agents, among many other commercial applications. The global distribution and environmental persistence of these compounds has generated considerable interest regarding potential toxic effects. We have previously reported that perfluorooctanesulfonamidoacetate (FOSAA) and N-ethylperfluorooctanesulfonamidoacetate (N-EtFOSAA) induce the mitochondrial permeability transition (MPT) in vitro. In this study we tested the hypothesis that FOSAA and N-EtFOSAA interact with the adenine nucleotide translocator (ANT) resulting in a functional inhibition of the translocator and induction of the MPT. Respiration and membrane potential of freshly isolated liver mitochondria from Sprague-Dawley rats were measured using an oxygen electrode and a tetraphenylphosphonium-selective (TPP+) electrode, respectively. Mitochondrial swelling was measured spectrophotometrically. The ANT ligands bongkregkic acid (BKA) and carboxyatractyloside (cATR) inhibited uncoupling of mitochondrial respiration caused by 10 [mu]M N-EtFOSAA, 40 [mu]M FOSAA, and the positive control 8 [mu]M oleic acid. ADP-stimulated respiration and depolarization of mitochondrial membrane potential were inhibited by cATR, FOSAA, N-EtFOSAA, and oleic acid, but not by FCCP. BKA inhibited calcium-dependent mitochondrial swelling induced by FOSAA, N-EtFOSAA, and oleic acid. Seventy-five micromolar ADP also inhibited swelling induced by the test compounds, but cATR induced swelling was not inhibited by ADP. Results of this investigation indicate that N-acetyl perfluorooctane sulfonamides interact directly with the ANT to inhibit ADP translocation and induce the MPT, one or both of which may account for the metabolic dysfunction observed in vivo.